Pengaruh Model Problem Based Learning(PBL) Integrasi ChatGPT terhadap Kemampuan Berpikir Kreatif Mahasiswa PAI UIN Mataram - Mauzifa Mauzifa; Baehaqi Baehaqi (Al-Ahnaf: Journal of Islamic Education, Learning and Religious Studies, 2025)
This study aims to analyze the application of the Problem-Based Learning (PBL) model integrated with ChatGPT media in the teaching of Contemporary Fiqh courses, specifically the material "Pornography and Pornoaction in the Islamic Perspective" for fourth-semester students of the Islamic Education at UIN Mataram. Specifically, this study examines the effect of integrating PBL and ChatGPT on students' creative thinking abilities. The theoretical basis of this study refers to the stages of the PBL model according to Hmelo-Silver, including problem presentation, analysis and identification of learning needs, independent learning, synthesis and solution development, and evaluative reflection. The indicators of creative thinking are based on Guilford's theory, namely fluency, flexibility, originality, and elaboration of thinking. The method used is a quasi-experiment with data collection techniques through tests, questionnaires, interviews, observations, and documentation. Data analysis was conducted quantitatively, including validity and reliability tests of the instruments, normality and homogeneity tests, and hypothesis testing using Mann Whitney and Spearman Rank to see the effect and direction of the relationship between variables. The results of the study showed that the application of the ChatGPT-integrated PBL model improved the quality of Contemporary Fiqh learning. Students became more active, responsive, and adaptive in the learning process. Students' creative thinking skills also experienced a significant increase, especially in terms of fluency, flexibility, uniqueness, and detail in responding to contemporary fiqh issues. Keywords: Problem Based Learning; ChatGPT; Creative Thinking